Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
a) 2(x+3)-x=4x
2x+6-x=4x
6=4x+x-2x
6=3x
x=2
b) 3x-4=x+9
3x-x=9+4
2x=13
x=[tex]\frac{13}{2}=6\frac{1}{2}[/tex]
c) -3(x-5)=x-7
-3x+15=x-7
-x-3x=-7-15
-4x=-22
x=5,5=[tex]5\frac{1}{2}[/tex]
d) 2(x+1)+6=4(2-3x)-4
2x+2+6=8-12x-4
2x+12x=-4+8-6-2
14x=-4
x=[tex]-\frac{2}{7}[/tex]
Odpowiedź:
a) x=2 b)x=2,5 c)x=-2 d) x=-2/7
Szczegółowe wyjaśnienie:
a) 2(x+3)-x=4x
2x+6-x=4x
2x-x-4x=-6
-3x=-6 /:-3
x=2
b)3x-4=x+9
3x-x=9+4
2x=13 /:2
x=6,5
c) -3(x-5)=x-7
-3x+15=x-7
-3x-x=-7-15
-4x=-22 /:-4
x=5,5
d)2(x+1)+6=4(2-3x)-4
2x+2+6=8-12x-4
2x+12x=4-8
14x=-4 /:14
x=-2/7